2020
DOI: 10.21037/gs-20-451
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric nutritional risk index serves as risk factor of surgical site infection after pancreatoduodenectomy: a validation cohort Ageo study

Abstract: Background: Surgical site infections (SSIs), which are associated with preoperative malnutrition, are a well-known potential complication of surgery that leads to increased medical costs and longer hospitalizations. Thus, surgeons need to accurately identify patients at high-risk for SSIs. Considering that the Geriatric Nutritional Risk Index (GNRI) was designed to assess the degree of malnutrition specifically among elderly patients, previous evidence (Kawaguchi study) proved that GNRI predicted the risk of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…For example, several studies indicated that albumin was a significant risk factor for hospital‐acquired pneumonia (Dziedzic et al., 2006 ; Yang et al., 2020 ). Besides, another study found that GNRI was a risk factor for surgical site infection after pancreaticoduodenectomy (Funamizu et al., 2020 ). In the present study, GNRI was an independent risk factor for SAP in AIS patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies indicated that albumin was a significant risk factor for hospital‐acquired pneumonia (Dziedzic et al., 2006 ; Yang et al., 2020 ). Besides, another study found that GNRI was a risk factor for surgical site infection after pancreaticoduodenectomy (Funamizu et al., 2020 ). In the present study, GNRI was an independent risk factor for SAP in AIS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The GNRI score is a simple scale system initially designed to assess malnutrition risk among elderly patients ( 22 ). Subsequently, the GNRI score was applied to predict sepsis mortality ( 32 ) and the probability of surgical site infections ( 33 , 34 ). Malnutrition risk was found in 5.3% of 8,698 Chinese patients with AIS according to the GNRI score ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…has reported that a lower GNRI score was independently associated with an increased risk of infection-associated mortality in patients receiving hemodialysis [27]. Other studies have also demonstrated that a poor nutritional status indicated by a lower GNRI score was also associated with an increased risk of surgical site infection after pancreatoduodenectomy and soft tissue sarcoma resection, while the infection risk could be effectively reduced with nutritional intervention during the perioperative period [28,29]. Likewise, we have reported a signi cant association between a lower GNRI score and a higher risk of invasive candidiasis.…”
Section: Discussionmentioning
confidence: 99%